PRODUCTION BEHAVIOUR OF UNDERSIZE SEED TUBERS OF POTATO UNDER VARYING PLANT DENSITIES IN NORTH-WESTERN HELLS OF INDIA - Sharma, Ashwani Kumar; Singh, Sarjeet (Potato Journal, 2013)
Production potential of small (10g) seed tubers of four potato varieties of hills viz., Kufri shailja, Kufri Kanchan, Kufri giriraj and Kufri Jyoti was evaluated at three plant densities viz., 83,333; 111,111 and 166,666 plants/ha. plant vigour in respect of height, number of shoots and compound leaves was affected significantly by the varying plant densities as well as by the genotypes. days to foliage maturity were not influenced by the plant densities but varieties differed significantly. number of total and seed size tubers were maximum in Kufri shailja (6.09 and 3.33 lakh/ha, respectively) at the maximum plant density (166,666 plants/ha) and minimum in Kufri Jyoti (2.36 and 1.00 lakh/ha respectively) at the minimum plant density. similarly, total and seed size tuber yields were maximum in Kufri shailja (369.0 and 175.8 q/ha) at the maximum plant density. potato yields were minimum in Kufri Jyoti (242.6 q/ha) at minimum plant density, whereas seed size tuber yield was minimum (55.3 q/ha) in Kufri giriraj but at par with Kufri Jyoti.